Cameras in the courtroom : television and the pursuit of justice - Cohn, Marjorie, 1948-; Dow, David, 1937- (Jefferson, N.C. : McFarland, 1998)
Presents a variety of viewpoints on the issue of cameras in the courtroom, drawing from interviews with judges, attorneys, jurors, witnesses, scholars, and journalists in an attempt to reach a balance between the public's right to know and a defendant's right to a fair trial.
Includes bibliographical references (p. 163-181) and index.
Choice.
Reference and Research Book News.
Adult
Keywords: Conduct of court proceedings -- United States; Television broadcasting of news -- Law and legislation -- United States; Legal etiquette; Television broadcasting of news -- Law and legislation